The effects of plate stiffeners on the ultimate load of square concrete-filled double-skin tubular (CFDST) short column - Mohd Reza Azmi; Chang, Zheng Hao; Mohd Yazmil Md. Yatim; Ong, Tze Sean (Penerbit Universiti Kebangsaan Malaysia, 2024)
This paper studies the effects of plate stiffeners on the ultimate load of square concrete-filled double-skin tubular (CFDST) short columns under axial compression. The study determines and compares the load-bearing capacity of concrete-filled steel tubular (CFST) short column, CFDST short column and CFDST short columns with plate stiffeners. To achieve these objectives, the researchers performed experimental tests on six composite column specimens: one CFST short column, one CFDST short column and four CFDST short columns with plate stiffeners. The stiffeners are welded to the inner surface of the external tube through pre-drilled holes systematically spaced at four spacings of 10t, 20t, 30t, and 40t, with t represents the external tube thickness. The test results show that the internal steel tubes increased the ultimate strength of the CFDST short columns by approximately 11% compared with the CFST short columns. The CFDST short column with plate stiffeners showed a significant strength improvement of 33% - 42% relative to the CFDST short column. The ultimate strength of CFDST short columns with plate stiffeners increased with smaller intermittent weld spacing of plate stiffeners. Finally, this study proposes a design model that can accurately predict the ultimate strength of CFDST short columns with plate stiffeners with a predicted to experimental strength ratio of 1.02.